The Plea Bargain Concept Related to Medical Malpractice Crimes to Realize Substantive Justice: An Idea for the Future - Darma, I Made Wirya; Waeno, Mahamadaree (Magister of Law, Faculty of Law, University of Mataram, 2023)
Malpractice in medical practice is a common thing that occurs because the unprofessionalism and negligence of medical personnel and . In practice, medical malpractice is resolved through a convoluted criminal justice system that does not reflect a substantive justice orientation. This study aims to formulate the idea of applying plea bargaining in the settlement of criminal acts related to medical malpractice in order to realize substantive justice. The results of the study confirm that the settlement of criminal acts related to medical malpractice does not reflect substantive justice and is not oriented toward efforts to provide compensation for victims. Therefore, in the future, efforts are needed to apply the concept of a plea bargain in the settlement of criminal acts related to medical malpractice in order to ensure substantive justice for victims of medical malpractice.